Granulomatous reactions cause symptoms or clinically imitate treatment resistance in small lymphocytic lymphoma/chronic lymphocytic leukaemia more frequently than in other non-Hodgkin lymphomas. Issue 8 (27th July 2005) - Brunner, A; Kantner, J; Tzankov, A
Abstract : Aims: The electronic database of the institute of pathology, Medical University of Innsbruck, was reviewed and patient histories studied to analyse systematically the coincidence of granulomatous reactions and lymphomas in a large patient collective, and to find distinct clinicopathological correlations. Five cases of small lymphocytic lymphoma/chronic lymphocytic leukaemia (CLL) associated with granulomatous reactions in lymph nodes and bone marrow were identified, all clinically associated with signs of progressive disease. Methods: Cases were acquired by reviewing an electronic database comprising approximately 715 000 patients diagnosed between 1993 and 2003. Histochemical, immunohistochemical, and molecular techniques were used to verify diagnosis and associated infectious diseases. Clinical data were obtained from reviewing the charts. Results: Of 2044 bone marrow and 411 lymph node non-Hodgkin lymphoma biopsy samples, CLL was most frequently associated with bone marrow (two cases) and lymph node granulomas (three cases). These granulomas were mostly composed of epithelioid cells, with or without giant cells, and in all but one case did not show necrosis. All patients with CLL had clinical symptoms primarily caused by the granulomatous disease: two suffered from acid fast bacilli infections ( Mycobacterium tuberculosis and mycobacteria other than tuberculosis) and three presented with clinical manifestations of sarcoidosis (the reason a diagnostic biopsy was performed). Conclusions: Granulomatous reactions in patients with CLL might obscure diagnosis and imitate disease progression and Richter's transformation. Careful histological examination, exclusion of infectious agents, and a detailed clinical history are essential for correct diagnosis.